2020
DOI: 10.1002/cpmc.132
|View full text |Cite
|
Sign up to set email alerts
|

Gene Editing in Dimorphic Fungi Using CRISPR/Cas9

Abstract: Dimorphic fungi in the genera Blastomyces, Histoplasma, Coccidioides, and Paracoccidioides are important human pathogens that affect human health in many countries throughout the world. Understanding the biology of these fungi is important for the development of effective treatments and vaccines. Gene editing is a critically important tool for research into these organisms. In recent years, gene targeting approaches employing RNA‐guided DNA nucleases, such as clustered regularly interspaced short palindromic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…Previously Yps-3 RNAi knockdown had shown no yeast phenotype in a macrophage cell line [ 34 ]. Since RNAi may not be definitive, to further characterize the role of Yps-3 in macrophage infection we generated a CRISPR deletion mutant of YPS-3 ( S7A and S7B Fig ) [ 52 , 53 ]. We found that the yps-3Δ mutant has a partial lysis defect in BMDMs ( Fig 6D ) despite the presence of Cbp1 in the cytosol of macrophages infected with this mutant ( Fig 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…Previously Yps-3 RNAi knockdown had shown no yeast phenotype in a macrophage cell line [ 34 ]. Since RNAi may not be definitive, to further characterize the role of Yps-3 in macrophage infection we generated a CRISPR deletion mutant of YPS-3 ( S7A and S7B Fig ) [ 52 , 53 ]. We found that the yps-3Δ mutant has a partial lysis defect in BMDMs ( Fig 6D ) despite the presence of Cbp1 in the cytosol of macrophages infected with this mutant ( Fig 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…Since RNAi may not be definitive, to further characterize the role of Yps-3 in macrophage infection we generated a CRISPR deletion mutant of YPS-3 (Fig. S8A and B) (53,54). We found that the yps-3∆ mutant has a partial lysis defect in BMDMs (Fig.…”
Section: Hc G217b and Pb03 Cbp1 Enter The Cytosol During Macrophage Infectionmentioning
confidence: 99%
“…To overcome the existing limitations of current technologies for loss-of-function studies in Histoplasma and related dimorphic fungi, there has been considerable interest in and early work to apply CRISPR/Cas genome editing ( 22 ). We describe an optimized system for the expression of gene targeting crRNAs by Pol(II)-based transcription of a single chimeric guide RNA (gRNA or sometimes referred to as sgRNA) consisting of the crRNA and tracrRNA in one molecule.…”
Section: Introductionmentioning
confidence: 99%